Games Workshop Company-based Dissertation Developing An Alternative Business Model For Delivering Games Workshop Digital Products - Li, Alan/S (2013)
Games Workshop has significant brand recognition around the world as the premier tabletop gaming brand. Their three main franchises, Warhammer 40,000, Warhammer Fantasy Battles and Lord of the Rings Tactics have widespread appeal across many demographic groups. One of the key factors that contributed to the success of their brand is the publications created by their Black Library publishing arm, which creates the novelizations, army books and a range of other publications that breathes life into the company's core products, the miniatures. Thus a good business model for the sales and distribution of Black Library publications are of paramount importance to the business. With the advancement in digital publishing market, there now exists new methods for Games Workshop to offer their digital non-magazine based product, and this project is commissioned to study the viability of one of the available alternative models, the digital subscription model. This study will involve a full literature review conducted around existing research from the consumer behaviour, pricing and brand communities literatures, which will provide insight into how a series of semi-structured interviews are conducted. The responses of the interviews should hopefully provide Games Workshop with an idea of how their customer base will respond to this alternative offering.